Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the explicit formula for the sequence [tex]\(-19, -28, -37, -46, \ldots\)[/tex], we need to identify the common difference and the first term, then use these to form the general formula for the [tex]\(n\)[/tex]-th term of the arithmetic sequence.
### Step-by-Step Solution:
1. Identify the common difference, [tex]\(d\)[/tex]:
- Find the difference between consecutive terms in the sequence.
- Second term: [tex]\(-28\)[/tex], First term: [tex]\(-19\)[/tex]
[tex]\[ d = -28 - (-19) = -28 + 19 = -9 \][/tex]
- Third term: [tex]\(-37\)[/tex], Second term: [tex]\(-28\)[/tex]
[tex]\[ d = -37 - (-28) = -37 + 28 = -9 \][/tex]
- Fourth term: [tex]\(-46\)[/tex], Third term: [tex]\(-37\)[/tex]
[tex]\[ d = -46 - (-37) = -46 + 37 = -9 \][/tex]
- Hence, the common difference is [tex]\(d = -9\)[/tex].
2. Identify the first term, [tex]\(a_1\)[/tex]:
- The first term of the sequence is given as [tex]\(-19\)[/tex].
3. Formulate the general term, [tex]\(a_n\)[/tex]:
- The general formula for an arithmetic sequence is given by:
[tex]\[ a_n = a_1 + (n-1)d \][/tex]
- Substituting [tex]\(a_1 = -19\)[/tex] and [tex]\(d = -9\)[/tex]:
[tex]\[ a_n = -19 + (n-1)(-9) \][/tex]
- Simplify the expression:
[tex]\[ a_n = -19 + (-9n + 9) \][/tex]
[tex]\[ a_n = -19 - 9n + 9 \][/tex]
[tex]\[ a_n = -10 - 9n \][/tex]
4. Evaluate the given options:
- [tex]\(a_n = -10-9n\)[/tex]
- [tex]\(a_n = -10+9n\)[/tex]
- [tex]\(a_n = -19-9n\)[/tex]
- [tex]\(a_n = -19+9n\)[/tex]
Comparing our simplified general formula [tex]\(-10 - 9n\)[/tex] with the given options, we can see that the exact match is:
[tex]\[ a_n = -19 - 9n \][/tex]
Thus, the correct explicit formula for the given sequence is:
[tex]\[ \boxed{a_n = -19 - 9n} \][/tex]
### Step-by-Step Solution:
1. Identify the common difference, [tex]\(d\)[/tex]:
- Find the difference between consecutive terms in the sequence.
- Second term: [tex]\(-28\)[/tex], First term: [tex]\(-19\)[/tex]
[tex]\[ d = -28 - (-19) = -28 + 19 = -9 \][/tex]
- Third term: [tex]\(-37\)[/tex], Second term: [tex]\(-28\)[/tex]
[tex]\[ d = -37 - (-28) = -37 + 28 = -9 \][/tex]
- Fourth term: [tex]\(-46\)[/tex], Third term: [tex]\(-37\)[/tex]
[tex]\[ d = -46 - (-37) = -46 + 37 = -9 \][/tex]
- Hence, the common difference is [tex]\(d = -9\)[/tex].
2. Identify the first term, [tex]\(a_1\)[/tex]:
- The first term of the sequence is given as [tex]\(-19\)[/tex].
3. Formulate the general term, [tex]\(a_n\)[/tex]:
- The general formula for an arithmetic sequence is given by:
[tex]\[ a_n = a_1 + (n-1)d \][/tex]
- Substituting [tex]\(a_1 = -19\)[/tex] and [tex]\(d = -9\)[/tex]:
[tex]\[ a_n = -19 + (n-1)(-9) \][/tex]
- Simplify the expression:
[tex]\[ a_n = -19 + (-9n + 9) \][/tex]
[tex]\[ a_n = -19 - 9n + 9 \][/tex]
[tex]\[ a_n = -10 - 9n \][/tex]
4. Evaluate the given options:
- [tex]\(a_n = -10-9n\)[/tex]
- [tex]\(a_n = -10+9n\)[/tex]
- [tex]\(a_n = -19-9n\)[/tex]
- [tex]\(a_n = -19+9n\)[/tex]
Comparing our simplified general formula [tex]\(-10 - 9n\)[/tex] with the given options, we can see that the exact match is:
[tex]\[ a_n = -19 - 9n \][/tex]
Thus, the correct explicit formula for the given sequence is:
[tex]\[ \boxed{a_n = -19 - 9n} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.